The Stratigraphic Distribution of Neogene Dinoflagellate Cysts from A Deep Water Well, Offshore Sabah, Northern Borneo - Huibert van den Brink (Berita Sedimentologi, 2019)
A research project was initiated with the objective to establish a dinoflagellate cyst biozonation for deep water wells drilled offshore Sabah and Brunei, Northern Borneo, to complement the biozonations based on nannoplankton, foraminifera and spores-pollen.Analysis of dinoflagellate cysts in ditch cutting samples from deep water well Kebabangan-1, offshore Sabah, resulted in a list of FDO’s, which could be of stratigraphic value: Hystrichokolpoma rigaudiae at 3150’, Operculodinium sp. A at 3840’, Dapsilidinium pastielsii at 4140’ and Lingulodinium pycnospinosum at 4950’ within the Pliocene section; Selenopemphix brevispinosa subsp. conspicua at 5760’ and consistent occurrence of Achomosphaera sp. B at 5760’ within the Upper Miocene section. Samples from appraisal well Kebabangan-2 were examined for calibration.Dinoflagellate cysts have been recovered from mud-rich shelfal topsets and underlying mud-rich slope fan systems in the interval 2610’ to 6495’, while the basal sand-rich base-of-slope fans in the interval 6705’ to 7905’ were barren of palynomorphs. A dinoflagellate biozonation is not yet proposed based on analyses of one well and cursory examination of the appraisal well. The correlation potential of the FDO’s reported for this well needs to be confirmed in follow-up wells along the Northern Borneo offshore.